Mixed messages mediating native belonging in Asian Russia - Graber, Kathryn Elizabeth (Cornell University Press, 2020)
Focusing on language and media in Asian Russia, particularly in Buryat territories, Mixed Messages engages debates about the role of minority media in society, alternative visions of modernity, and the impact of media on everyday language use. Graber demonstrates that language and the production, circulation, and consumption of media are practices by which residents of the region perform and negotiate competing possible identities. What languages should be used in newspapers, magazines, or radio and television broadcasts? Who should produce them? What kinds of publics are and are not possible through media? How exactly do discourses move into, out of, and through the media to affect everyday social practices? Mixed Messages addresses these questions through a rich ethnography of the Russian Federation's Buryat territories, a multilingual and multiethnic region on the Mongolian border with a complex relationship to both Europe and Asia.Mixed Messages shows that belonging in Asian Russia is a dynamic process that one cannot capture analytically by using straightforward categories of ethnolinguistic identity